Nilai Dakwah Dalam Tradisi ‘Nyadran’ Sebagai Upaya Penguatan Kearifan Lokal dan Budaya Islam - Ghofir, Jamal; Abdul Jabbar, Mohammad (Department of Da'wah Management, Faculty of Da'wah, IAINU Tuban, 2025)
The nyadran tradition is one of the traditions that still exists in this era of development, especially in the Java area, especially in the Plumpang area of ​​Tuban. In the nyadran tradition itself there are several rituals that must be carried out when carrying out the nyadran tradition ceremony. Namely, the first is burial clothes, the second is nyadran slametan and the third is sinden and shadow puppet shows throughout the night. There are several interesting things related to nyadran traditional ceremony activities in Plumpang Village, usually the Muslim community who carry out nyadran. This time it was very different because the people who carried out nyadran were Muslims, non-Muslims and isam kejawen. Nyadran is a symbol of the relationship between ancestors, nature and each other. This is a ritual pattern that contains local culture and Islamic values. So do not be surprised if the implementation of Nyadran is still related to Buddhist and Hindu culture or Animist beliefs which were then assimilated by Islamic values ​​by Wali Songo. To facilitate this research, researchers used qualitative research methods. This research was conducted in the Hamlet of Tanggungan, Plumpang Village, Tuban City. Observations and in-depth interviews were conducted to collect data.